2019
DOI: 10.5578/turkjsurg.4113
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic values of procalcitonin and interleukin 6 in acute appendicitis

Abstract: Objective: Despite the recent use of computed tomography scan and diagnostic laparoscopy, acute appendicitis is still highly misdiagnosed. Timely diagnosis of acute appendicitis is more crucial in children and elderly patients because of vague symptoms and rapid progression to perforation in these age groups, which may result in high rates of morbidity and mortality. The aim of the present study was to find the diagnostic values of procalcitonin and interleukin 6 (IL-6) for diagnosing acute appendicitis in our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
(12 reference statements)
1
11
0
1
Order By: Relevance
“…PCT showed an Sn and Sp of 65% and 80%, respectively, suggesting a possible role in AA diagnosis. Finally, the authors highlighted how simultaneous high levels of PCT and IL-6 achieve an Sn of 95% and Sp of 55% [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCT showed an Sn and Sp of 65% and 80%, respectively, suggesting a possible role in AA diagnosis. Finally, the authors highlighted how simultaneous high levels of PCT and IL-6 achieve an Sn of 95% and Sp of 55% [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Haghi et al reported that combining PCT and IL-6 improved the diagnostic efficiency of infectious appendicitis and decreased unnecessary negative appendectomies [Haghi 2018]. Another study demonstrated that the combination of IL-6, CRP and PCT seems to be predictive in diagnosis of early onset neonatal sepsis [Abdollahi 2012].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is a proinflammatory cytokine, mediator of acute phase reaction, and is secreted during inflammatory process and neutrophil recruitment following the invasion of bacteria to the appendix [14,15]. Some of the previous studies have shown its relatively high sensitivity (73-84%) and low specificity (46-72%) for diagnosing AA and even higher sensitivity (up to 91%) and lower specificity (37%) for diagnosing perforated appendicitis [16,17]. Elevated serum IL-6 levels were found in the majority of our patients (55, 82.09%, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%